“MICI DE OAIE” OR “COSTESINE E POENTA”?: THE USE OF URBAN PUBLIC GREEN SPACE BY NEW AND OLD RESIDENTS. THREE ITALIAN CASE STUDIES - Borghi, Rachele; Camuffo, Monica (Geo UERJ, 2011)
doi: 10.12957/geouerj.2011.2065